School Partnership Management with The Students’ Parents During the Online Distance Learning Period - Sophia Tri Satyawati; Wasitohadi Wasitohadi; Nuzul Triprastiwi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This research aims to explain the stages of planning, implementation, monitoring, and evaluation of the school partnership program with parents during distance learning. This research used qualitative and descriptive approaches. The subjects are the school principal, five subject teachers, one deputy principal, two representatives of students' parents, one head of administration, and two school committee members. The data are collected using participatory observation, in-depth interviews, documentation studies, and Focus Group Discussion (FGD). The data are analyzed through three steps, namely data reduction, data presentation, and drawing conclusions or verification. The findings indicate that during the planning stage, the partnership team has prepared some actions such as 1) first-day school activities; 2) parental activities; 3) inspirational activities; 4) parents’ involvement in self-development activities and 5) social activities. At the implementation stage, the school partnership team, along with the students’ parents, carries out some activities which involve the parents' association and school committee members based on the action plan that has been set previously. The monitoring process shows that the partnership program involves the parents' associations, the school committee members, and the teachers. The evaluation step shows that the action plan has been implemented effectively despite some issues.